Dynamics and Challenges of Democracy in Local Elections in Indonesia and the Netherlands - Hargono Hargono; Ahmad Rustan; Fachmi Jambak; La Ode Alba; Rofi Aulia Rahman (SASI, 2024)
Introduction: Elections for regional heads and heads of government are one of the important aspects in building a democratic system that encourages citizen participation in the political process.